Wolf on the wild side - Spear, Terry (Spear, Terry. Run with the wolf, 2023)
Two wolves are better than one, but a pack of wolves beats trouble any day... Ski Lodge owner and gray wolf Kayla Wolff hasn't had the best romantic history, so dating Private Investigator and fellow pack mate Nate Grayson feels like she's hit the jackpot. When she thinks about the way her last relationship ended, Kayla worries that she'll screw up again and lose Nate too. When Nate's latest investigation puts Kayla in the crosshairs, the pack comes together to help while Nate stays by her side day and night to protect the wolf he loves. There's no doubt in his mind that Kayla is the mate for him, but does she feel the same way?